Effect of gooseberry (Emblica officinalis) and Indian gall nut (Terminalia chebula) on the immune response in cockerels under induced heat and cold stress - Mejo K R (Department of Veterinary Physiology, College of Veterinary and Animal Science, 2006)
The study was conducted with an objective of finding the physiological and immunological variations that could be brought about with heat /cold stress in cockerels and the role of Gooseberry (GB) and Indian gallnut (IGN) supplementation as an antistress. Gramapriya cockerels of 1kg bw (3-4 months) were subjected to heat (40 ±1o C and relative humidity (RH) 60-70 percent) and cold stress (8 ±1o C and RH 40-50 per cent) each for 4h/day in a controlled environmental chamber (floor space 875 cm2 /bird) for a maximum of 10 days and the controls were reared randomly under ambient temperature of 30±1o C and RH 65 percent. GB+IGN supplementation was done @ 2.0 g/kg for 20 days (prior to and during the period of heat/cold stress). To a certain extend alternations in haematological parameters such as haemoglobin, packed cell volume, H/L ratio, biochemical parameters such as serum total protein, albumin, globulin, C-reactive protein, electrolytes like sodium and potassium, enzymes like lactate dehydrogenase and creatine kinase, cortisol, triiodothyronine (T3), thyroxine (T4) could be reversed by GB+IGN supplementation during heat stress. In the present study, the haemagglutinin (HA), hemolysin (HL), IgG and IgM titres and the spleenic antibody forming cells (plaque forming cells) and rosette forming cells (RFC) against known antigen were studied. The results indicated that GB+IGN supplementation not only maintained the preformed antibody titre but also improved the humoral immune response against a challenged antigen during the period of heat stress. In the present study, it was found that during cold stress, the GB+IGN supplementation could bring about an early tendency to restore the normal homeostasis of haematological, biochemical, and hormonal parameters. Cold stress resulted in a low profile of humoral immune response indicated by low anti-SRBC haemolysin (HA), Haemolysin (HL), IgG and IgM titres in untreated, CST cockerels when compared to GB+IGN treated counterparts, which showed better tires during cold stress. Similarly, treated cockerels exhibited more spleenic cells that produce antibodies against rat red blood cells. Thus, the immunopotentiative property of GB+IGN was reconfirmed and that the drug supplementation stimulated the humoral arm of immunity in cold stressed cockerels. Results of the present study indicated that combined supplementation of GB+IGN @ 2.0 g/kg bw in poultry could augment the humoral response during heat and cold stress.